A rare case of life threatening non-obstetric-non-traumatic vulvar-vaginal haematoma secondary to suspected spontaneous rupture of the right pudendal artery: surgical management in a reference hospital in Southern Nigeria - Eze, Innocent Okafor; Anyanyu, Noble Chidiebere; Nzeribe-Abangwu, Ugochi Ogbonneya; Igboezue, Victor Cletus; Muhammed, Rufai; Uzoho, David Ugonna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Vulvar haematoma due to obstetrics and traumatic causes have been reported. However, non-obstetrics-non-traumatic vulvar-vaginal haematoma is very rare yet could be life threatening. Good management and outcome may be challenged by low index of suspicion, inexperience and lack of standard guideline for care. We report a rare case of life threatening non-obstetric-non-traumatic vulvar-vaginal haematoma secondary to suspected spontaneous rupture of the right pudendal artery in a 35-year-old woman which presented as emergency with diagnostic challenges and was successfully surgically managed. This report draws attention of clinicians to this rare but important clinical scenario which can present with diagnostic challenges. It further highlights different approaches to treatment but emphasizes surgical treatment as key to quick recovery with lesser morbidities.